The Comparison of Personality Traits, Forgiveness, and Resilience Among Patients with Cancer and Healthy Persons - Dashtipour 1, Marjan; Vahedi 2*, Hamid; Taher 1, Mabobeh (Shahroud Journal of Medical Sciences, 2019)
Background: This research purpose was to compare the HEXACO personality traits, forgiveness and resilience between the cancer patients and healthy people.Methods: In this comparative study, the research samples included 100 cancer patients and 100 healthy people with the age of 30 to 55 years old during 2017 in Shahroud city. HEXACO Personality Inventory, Forgiveness Scale of Walker and Gorsuch (2002) and Connor-Davidson Resilience Scale (2003) were used in order to collect data. Data were analyzed using a multivariate analysis of covariance (MANCOVA).Results: The multivariate analysis of covariance results indicated that HEXACO personality traits had a lower mean score in two dimensions (conscientiousness and openness to experience)amongst people with cancer. It was also established that people with cancer had a higher mean score in the lasting resentment dimension. The results also demonstrated that there is a significant difference between the two groups resilience.Conclusions: It is crucial to pay more attention to the psychological factors role like personality traits, forgiveness and resilience in the cancer formation and promotion.